ANALISIS PENGENDALIAN BIAYA PRODUKSI MINYAK SAWIT (CPO) PADA PT. CAHAYA ANUGERAH PLANTANTION TAHUN 2014 - 2017 - Ramadanil, - - (EKONOMIA, 2019)
Ramadanil : Analysis of production cost control palm oil (CPO) on PT. Cahaya Anugerah Plantantion in 2014 â€“ 2017. Under the guidience of Mrs. Titin Ruliana as supervising lecture I and Mr. Murfat Effendi as supervising lecture II.The purpose of this research is to find out whether production cost budget, and realization that focuses on the level efficiency cost production palm oil (CPO) onÂ PT. Cahaya Anugerah Plantantion in 2014 until 2017.This research method that is using quantitative data and hypothesis of this research is production cost control palm oil (CPO) on PT. Cahaya Anugerah Plantantion in 2014 â€“ 2017 already efficient.Result of research from analysis of palm oil production cost control at PT. Cahaya Anugerah Plantantion (CPO) in 2014 to 2017 already efficient with efficiency level category less than 100% so the hypothesis of this research in accepted.Based on the result and the above discussion can be concluded that production cost control already planned and well executed, the role of control is determines good or bad implementation of a plan